The effectiveness of using video and pictures in teaching writing hortatory exposition text - Adhan Kholis (LingTera, 2018)
This study aimed to find out the differences in the students’ achievement in writing the hortatory exposition text among the students taught by using video, pictures, and the lecturing method with the genre-based approach. This study was quasi-experimental research with the pretest and the posttest design. The sample consisted of grade eleven students of majoring science comprising three classes chosen by cluster random sampling. Two classes were for the experimental groups taught using video and pictures and the control group taught using the lecturing method. The data were collected using the test of writing. The validity established was the content validity, while the reliability used was inter-rater. Analysis of covariance (ANCOVA) was used to analyze data. The results of the study had shown that there were the significant differences between the experimental and the control groups where the use of video was the most effective media in teaching writing.